2003
DOI: 10.1016/s0024-3795(02)00734-6
|View full text |Cite
|
Sign up to set email alerts
|

The Schur algorithm for generalized Schur functions III: J-unitary matrix polynomials on the circle

Abstract: The main result is that for J = 1 0 0 −1 every J-unitary 2 × 2-matrix polynomial on the unit circle is an essentially unique product of elementary J-unitary 2 × 2-matrix polynomials which are either of degree 1 or 2k. This is shown by means of the generalized Schur transformation introduced in [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…In [4] it was shown that for J = 1 0 0 −1 aĴ -unitary 2 × 2 matrix polynomial on the unit circle admits an essentially unique factorization into elementaryĴ -unitary matrix polynomials. The essential tool was the theory of reproducing kernel Pontryagin spaces and the Schur algorithm for generalized Schur functions as developed in [2][3][4][5][6][7]12,14,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…In [4] it was shown that for J = 1 0 0 −1 aĴ -unitary 2 × 2 matrix polynomial on the unit circle admits an essentially unique factorization into elementaryĴ -unitary matrix polynomials. The essential tool was the theory of reproducing kernel Pontryagin spaces and the Schur algorithm for generalized Schur functions as developed in [2][3][4][5][6][7]12,14,17,19].…”
Section: Introductionmentioning
confidence: 99%
“…In [8] it is applied to solve the problem: When is a formal power series around z = 0 the Taylor expansion of a generalized Schur function. In [1,2,4,6,17] it is studied for its effect on the coisometric and unitary operator realizations of a generalized Schur function, including those whose state spaces are the reproducing kernel Pontryagin spaces with kernels K s (z, w) and D s (z, w); in [3] it is shown to provide an algorithm for the unique factorization of a 2 × 2 matrix polynomial which is J-unitary on T (for the definition, see below) in normalized elementary factors; and, finally, in [5] (see also [12]) it is used in solving a basic interpolation problem for generalized Schur functions.…”
Section: The Function S(z) Admits the Krein-langer Factorizationmentioning
confidence: 99%
“…Heinz proposed that Aad, Henk, their student Piet Bruinsma and this editor consider the interpolation problem using Krein's formula and the theory of resolvent matrices for the description of the self-adjoint extensions of a given Hermitian operator (see [22,33]); this led in particular to the publications [4,5]. A bit later, collaboration between Aad, Heinz and DA began (mainly on the Schur algorithm for generalized Schur functions) and lead to seventeen publications, some of them written in collaboration with Thomas Azizov, R. Buursema, Simeon Reich, David Shoikhet, Yuri Shondin, Dan Volok, and Gerald Wanjala; see for instance [2,3,8,9,10]. The encounter, and the subsequent collaboration with Heinz was fascinating on numerous grounds.…”
Section: Telle Est La Morale Que Mermoz Et D'autres Nous Ont Enseignémentioning
confidence: 99%